An Analysis of Teacher’s Technique Speaking on Class During Covid-19 at Second Grade of Junior High School - Enzelina Sinaga; Ramauli Rajagukguk; Surliyah Ningsih; Rahma Wati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
AbstractThe title of this research is "An analysis Teacher's technique and Media in teaching speaking during Covid-19 at the second grade of SMP Swasta Amalyatul Huda Medan." In the Covid-19 pandemic situation, the government has announced online learning activities. The relationship between this policy and teacher learning strategies is interesting. Therefore, this study focuses on the method used by teachers in carrying out learning during the Covid19 pandemic, distance learning (PJJ). This will allow you to learn optimally, effectively, and correctly. This study aims to explain teacher techniques in teaching specs during the Covid19 pandemic. This study uses a descriptive qualitative approach. The subject is an English teacher class VIII. Data collection methods in this study were observation, interviews, and recording. Two learning methods are used when analyzing online teacher learning methods that support virtual media. One of them is the mapping method through the Google Classroom application; the results of the answer sheets are collected directly at the school, then the second learning method becomes a problem. Questions and answers via Zoom Meetings and WhatsApp groups. This study concludes that the teacher's strategy in teaching speaking at SMP Swasta Amalyatul Huda in Medan during the Covid19 pandemic can be seen in terms of educational goals, educational approaches, and methods.